Influence of inertial resistance squat exercise protocol based on novel exercise intensity determination on physical fitness of older adult women - Darjan Spudić; Vedran Hadžić; Janez Vodičar; Jamie Carruthers; Primož Pori (Exercise and Quality of Life)
The aim of the study was to examine practical implications and actual effects of the 8-week progressive resistance exercise protocol with the custom-made inertial device on sit-to-stand, 6- MWT, functional reach, up-and-go test results and Rate of Perceived exertion (RPE) among older adult women (age 65-74). Thirty-seven healthy volunteers were randomly assigned to the control group (n = 11) and to two exercise – inertial (n = 12) and traditional (n = 14) – groups. The participants performed hip belt squats on the inertial device and kettlebell squats, respectively. Exercise intensity was relatively adjusted using mass moment of inertia (MMI) of the cylindrical weight and %1RM. Time under tension was equalized between groups by the type of the exercise executed. Tests were performed before and after the intervention. Moreover, RPE was monitored after each exercise set. We used two-way repeated measures ANOVA to assess exercise-related differences in test results and to assess intensityrelated differences in RPE. The Senior Fitness Test results significantly differed in pre and post measurements, regardless of the group. A significant time x group interaction was only found in Sit-to-stand test results. RPE results significantly varied from each other across intensities. Statistically different results among groups were only found at the highest intensity (70%). The results indicate that inertial resistance exercise using the novel exercise intensity determination on the inertial device is a useful and less strenuous alternative to traditional resistance exercise among older adult women while performing squats.